Button-type battery and method of manufacturing the same
Patent Information
- Application Number
- CN202580023158.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-02-05
- Filing Date
- 2025-03-18
- Publication Date
- 2026-10-27
AI Technical Summary
[0002]纽扣型(硬币型)的锂二次电池、双电层电容器等电化学电池具有结构为在收纳有正极和负极这样的发电要素的外装罐与封口罐之间夹着树脂质的垫片而密封的电池容器,该纽扣型(硬币型)的锂二次电池、双电层电容器等电化学电池中,水分容易从电池容器的外部通过构成电池容器的外表面的一部分的垫片的露出部而侵入内部,由于该水分的影响而有可能无法长期维持性能
[0016]根据本发明,能够提供纽扣型电池及其制造方法,所述纽扣型电池具备具有外装罐、封口罐和树脂制的垫片的电池容器,能够良好地抑制水分从外部向内部侵入、水分从内部向外部散逸。
Smart Images

Figure CN122996548A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to button batteries and their manufacturing methods. The button batteries have a battery container with an outer can, a sealing can, and a resin gasket, which can effectively prevent moisture from entering from the outside to the inside and moisture from escaping from the inside to the outside. Background Technology
[0002] Button-type (coin-type) lithium secondary batteries, double-layer capacitors, and other electrochemical batteries have a battery container structure in which a resin gasket is sandwiched between an outer can containing power-generating elements such as positive and negative electrodes and sealed to form a battery container. In these button-type (coin-type) lithium secondary batteries, double-layer capacitors, and other electrochemical batteries, moisture can easily penetrate from the outside of the battery container through the exposed portion of the gasket, which forms part of the outer surface of the battery container, and may not be able to maintain its performance for a long time due to the influence of moisture. Therefore, for example, Patent Document 1 attempts to solve the above problem by filling the space formed by the positive electrode can, the negative electrode can (outer can and sealed can), and the gasket with a first resin with low viscosity and good flowability in liquid state, and having a second resin further filled on the first resin.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2007-35829 Summary of the Invention
[0006] The problem that the invention aims to solve
[0007] On the other hand, in alkaline batteries and similar devices that use alkaline electrolytes, nylon resins with excellent alkali resistance but high water permeability are used for the gaskets. Therefore, even though the battery contains an aqueous electrolyte solution, moisture can still seep into the battery through the gaskets, sometimes causing electrolyte leakage. Furthermore, in low-humidity environments, moisture can escape from the battery through the gaskets, reducing the electrolyte level and sometimes causing a decrease in battery capacity. Therefore, there is a need to develop technologies that effectively prevent moisture from seeping into the battery through the gaskets or escaping to the outside of the battery.
[0008] The present invention was made in view of the above circumstances, and its object is to provide a button cell battery and a method for manufacturing the same, wherein the button cell battery has a battery container having an outer can, a sealing can and a resin gasket, which can effectively inhibit the intrusion of moisture from the outside to the inside and the escape of moisture from the inside to the outside.
[0009] Methods for solving problems
[0010] The button-type battery of the present invention is characterized in that it has a battery container having an outer can and a sealing can, and a resin gasket between the outer can and the sealing can, wherein a resin coating is formed on the exposed surface of the gasket, and satisfies (1) or (2) below.
[0011] (1) The resin of the above-mentioned resin coating is a cured product of a light-curable olefin resin.
[0012] (2) The above-mentioned resin coating contains an olefin resin having a glass transition temperature of less than 30°C and an elongation of more than 300%.
[0013] In addition, the present invention provides a method for manufacturing a button cell battery, the button cell battery comprising a battery container having an outer can and a sealing can, and a resin gasket between the outer can and the sealing can, wherein a positive electrode, a negative electrode and an electrolyte are disposed inside the battery container. The method for manufacturing the button cell battery is characterized by comprising a step of sealing by sandwiching a resin gasket between the outer can and the sealing can, a step of forming a photocurable olefin resin coating layer on the exposed surface of the sealed gasket, and a step of curing the olefin resin.
[0014] It should be noted that in the battery industry, flat batteries with a diameter greater than their height are called button batteries or coin batteries. However, there is no clear difference between button batteries and coin batteries. The button battery of this invention does not exclude batteries that are called coin batteries. Such batteries are also included in the scope of the button battery of this invention.
[0015] Invention Effects
[0016] According to the present invention, a button cell battery and a method for manufacturing the same are provided. The button cell battery comprises a battery container having an outer can, a sealing can, and a resin gasket, which can effectively inhibit the intrusion of moisture from the outside to the inside and the escape of moisture from the inside to the outside. Attached Figure Description
[0017] Figure 1 This is a cross-sectional view schematically illustrating an example of a button cell battery according to the present invention.
[0018] Figure 2 This is a graph showing the change in discharge capacity of the button batteries of Example 3 and Comparative Example 3 under high-temperature storage. Detailed Implementation
[0019] Figure 1 A cross-sectional view is shown, schematically illustrating an example of a button-type battery according to the present invention. Figure 1The button cell battery 1 shown includes a battery container with an outer can 2, a sealing can 3, and a resin gasket 7 between the outer can 2 and the sealing can 3. The positive electrode 4 and the negative electrode 5 are sealed inside the battery container along with an electrolyte (not shown) in a stacked state separated by a separator 6. In the battery container of the button cell battery 1, the sealing can 3 is fitted into the opening of the outer can 2 with an L-shaped cross-section separated by the annular gasket 7. The opening end of the outer can 2 is tightened inwards, thereby abutting the gasket 7 against the sealing can 3, thus sealing the opening of the outer can 2 to form a closed structure.
[0020] like Figure 1 As shown, in the gasket 7 located between the outer can 2 and the sealed can 3, there is a portion (exposed surface) that is exposed to the outside of the battery container without contacting either the outer can 2 or the sealed can 3. Furthermore, in the button cell battery 1, external moisture may enter the battery container through the exposed surface of the gasket 7. Additionally, internal moisture may also escape from the exposed surface of the gasket 7 to the outside of the battery container.
[0021] Therefore, in the button cell of the present invention, as Figure 1 As shown, a resin coating layer 8 is formed on the exposed surface of the gasket 7 that satisfies either (1) or (2) below.
[0022] (1) The resin of the above-mentioned resin coating is a cured product of a light-curable olefin resin.
[0023] (2) The above-mentioned resin coating contains an olefin resin having a glass transition temperature of less than 30°C and an elongation of more than 300%.
[0024] If the resin coating satisfies (1) or (2), moisture is difficult to permeate. Furthermore, even if the gasket expands and contracts with battery charging and discharging, the cured photocurable olefin resin contained in the resin coating, or an olefin resin with a glass transition temperature below 30°C and an elongation of over 300%, can deform in accordance with its volume change, thus maintaining the moisture-blocking function based on the resin coating effectively. In the button cell of the present invention, through these effects based on the resin coating, the intrusion of moisture from the outside into the battery container and the leakage of moisture from the inside of the battery container to the outside can be effectively suppressed. Accordingly, in the button cell of the present invention, even when an electrolyte composed of an aqueous solution is used, leakage of electrolyte due to external moisture intrusion and reduction in discharge capacity due to moisture leakage to the outside can be suppressed.
[0025] The resin coating that satisfies (1) above is formed using a photocurable olefin resin containing a photocured product.
[0026] Cured products of photocurable olefin resins contained in resin coatings include, for example, substances formed by photocuring a photocurable resin composition comprising (a) a polymer (polymer or oligomer) having a main chain with structural units derived from isobutylene and at least one (meth)acryloyl group within its molecule and (b) a monomer having a (meth)acryloyl group. The term "(meth)acryloyl group" as used above and below refers to both acryloyl and methacryloyl groups. For example, the polymer described above may have at least one acryloyl group, may have at least one methacryloyl group, or may have both acryloyl and methacryloyl groups. The number of (meth)acryloyl groups in one molecule of the polymer described above may be 1 to 12.
[0027] Polymers containing an isobutylene backbone and at least one (meth)acryloyl group as component (a) can be synthesized, for example, by reacting terminal hydroxyl polyisobutylene with acryloyl chloride or methacryloyl chloride; by reacting terminal hydroxyl polyisobutylene with a compound having (meth)acryloyl and isocyanate groups; by reacting terminal hydroxyl polyisobutylene, a compound having isocyanate groups, and a compound having (meth)acryloyl and hydroxyl groups; by reacting terminal hydroxyl polyisobutylene with (meth)acrylic acid or a lower ester of (meth)acrylic acid using a dehydration esterification method or a transesterification method, etc. The term "(meth)acrylic acid" above refers to both acrylic acid and methacrylic acid.
[0028] Such polymers can be polyisobutylene having (meth)acryloyloxyalkoxyphenyl. Alternatively, the polymers can have structural units on the main chain of straight-chain or branched olefins with 1 to 12 carbon atoms, such as ethylene, propylene, and isoprene, together with structural units from isobutylene. The term "(meth)acryloyloxyalkoxyphenyl" is a general term for both acryloyloxyalkoxyphenyl and methacryloyloxyalkoxyphenyl.
[0029] The proportion of structural units derived from isobutylene in the polymer is preferably 70% by mass or more, more preferably 75% by mass or more, even more preferably 80% by mass or more, preferably 95% by mass or less, and more preferably 90% by mass or less.
[0030] Monomers having a (meth)acryloyl group as component (b) can be exemplified by (b1) monomers having both a (meth)acryloyl group and a hydroxyl group and (b2) monomers having a (meth)acryloyl group but not a hydroxyl group.
[0031] Monomers having (meth)acryloyl and hydroxyl groups as component (b1) include, for example, 4-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, etc.
[0032] Monomers having a (meth)acryloyl group but not a hydroxyl group as component (b2) include, for example, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, n-octadecyl (meth)acrylate, isooctadecyl (meth)acrylate, nonadecanyl (meth)acrylate, and (meth)acrylate. 3-Heptyl-1-decyl ester, isostearyl (meth)acrylate, stearyl (meth)acrylate, etc., are (meth)acrylates with alkyl groups; cyclohexyl (meth)acrylate, 4-butylcyclohexyl (meth)acrylate, dicyclopentyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenoxy (meth)acrylate, isobornyl (meth)acrylate, adamantane (meth)acrylate, dicyclopentenyl (meth)acrylate, tricyclodecanediethanol di(meth)acrylate, etc., are (meth)acrylates with alicyclic structures.
[0033] It should be noted that "(meth)acrylate" in the specific example of component (b) is a general term for acrylate and methacrylate.
[0034] Regarding the monomer having a (meth)acryloyl group as component (b), for example, one or more monomers having a (meth)acryloyl group and a hydroxyl group as component (b1) may be used, or one or more monomers having a (meth)acryloyl group but not a hydroxyl group as component (b2) may be used, or one or more of component (b1) and one or more of component (b2) may be used.
[0035] In a photocurable resin composition comprising component (a) and component (b), the content of component (b) is preferably 3 to 500 parts by mass relative to 100 parts by mass of component (a). Furthermore, in the case where the photocurable resin composition comprises both component (b1) and component (b2) as component (b), the content of component (b1) is 0.1 to 15 parts by mass relative to 100 parts by mass of component (a), and the content of component (c) is preferably 5 to 500 parts by mass.
[0036] In addition, a photoradical polymerization initiator is added to the above-mentioned photocurable resin composition. The photoradical polymerization initiator can be an acetophenone-based photoradical polymerization initiator (diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, benzoyladium dimethyl ketal, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)one, 1-hydroxycyclohexylphenyl ketone, 2-methyl-2-morpholino(4-thiomethylphenyl)propane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 2-hydroxy... Known photoradical polymerization initiators include 2-methyl-1-[4-(1-methylvinyl)phenyl]acetone oligomers, benzoin-based photoradical polymerization initiators, benzophenone-based photoradical polymerization initiators, thioxanthone-based photoradical polymerization initiators, acylphosphine oxide-based photoradical polymerization initiators (bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, etc.), and diacene-based photoradical polymerization initiators.
[0037] The content of the photoradical polymerization initiator in the above-mentioned photocurable resin composition is preferably 0.1 to 20 parts by weight relative to 100 parts by weight of component (a).
[0038] The above-mentioned photocurable resin composition may contain resin particles such as (meth)acrylic resin particles, polystyrene particles, styrene-olefin copolymer particles, polyethylene particles, and polypropylene particles. The content of resin particles in the above-mentioned photocurable resin composition is preferably 0.1 to 20 parts by weight relative to 100 parts by weight of component (a).
[0039] In the above-mentioned photocurable resin composition, inorganic fillers (such as amorphous silica), organic peroxides, curing accelerators, preservation stabilizers, antioxidants (such as butylated hydroxytoluene), light stabilizers, plasticizers, pigments, flame retardants, and surfactants may also be added.
[0040] Commercially available products, such as the UV-curable olefin resin "3175" manufactured by Tri-Bond Corporation, can be used as such photocurable resin compositions.
[0041] For the cured product of the photocurable olefin resin contained in the resin coating layer that satisfies (1) above, its glass transition temperature (Tg) is preferably 30°C or less, more preferably 25°C or less. Furthermore, there is no particular limitation on the lower limit of the Tg of the cured product of the photocurable olefin resin contained in the resin coating layer that satisfies (1) above, and it is generally -40°C or more. If the resin coating layer contains such a low Tg resin cured product, even if the gasket expands and contracts due to battery charging and discharging, the resin coating layer can deform more effectively in accordance with its volume change.
[0042] The Tg of the cured olefin resin that satisfies the photocurability of the resin coating layer described in this specification (1) and the Tg of the olefin resin that satisfies the resin coating layer described in (2) described later are determined by the change in expansion rate through thermomechanical analysis (TMA).
[0043] For the cured olefin resin containing the resin coating that satisfies the above (1), its elongation is preferably 300% or more, more preferably 400% or more. Furthermore, there is no particular limit to the upper limit of the elongation of the olefin resin contained in the resin coating that satisfies the above (1), and it is generally 900% or less. If the resin coating contains a cured resin with such a high elongation, even if the gasket expands and contracts due to battery charging and discharging, the resin coating can deform more effectively to follow its volume change.
[0044] The elongation of the cured olefin resin that satisfies the photocurability of the resin coating layer described in this specification refers to the elongation until breakage when a tensile test is performed using a tensile testing machine with a tensile speed of 500 mm / min on a test piece made by punching a sheet of the cured material with a thickness of 1.0 mm using a No. 3 dumbbell shape.
[0045] Accordingly, more preferably, the cured olefin resin contained in the resin coating layer that satisfies the above (1) has a Tg of 30°C or less and an elongation of 300% or more.
[0046] Cured products of photocurable olefin resins with Tg satisfying the aforementioned values and cured products of photocurable olefin resins with elongation satisfying the aforementioned values can be obtained by photocuring the aforementioned exemplified photocurable resin compositions.
[0047] The resin coating layer satisfying (2) above contains an olefin resin having a glass transition temperature of 30°C or lower and an elongation of 300% or higher. It should be noted that the olefin resin includes thermoplastic resins that melt or soften due to heat, and curable resins that are cured by heat, light, or the like. The olefin resin contained in the resin coating layer includes both thermoplastic and curable resins; however, in the case of curable resins, it includes not only the resin before curing but also the resin after curing (cured olefin resin). Furthermore, the aforementioned Tg and elongation of the olefin resin contained in the resin coating layer satisfying (2) above are values of the cured resin (cured olefin resin).
[0048] From the viewpoint of ensuring that the resin coating can deform well in response to changes in the volume of the gasket, the olefin resin contained in the resin coating satisfying (2) above has a Tg of 30°C or less, preferably 25°C or less. Furthermore, there is no particular limitation on the lower limit of the Tg of the olefin resin contained in the resin coating satisfying (2) above, and it is generally -40°C or more.
[0049] From the viewpoint of ensuring that the resin coating can deform well in response to changes in the volume of the gasket, the elongation of the olefin resin contained in the resin coating satisfying (2) above is 300% or more, preferably 400% or more. In addition, there is no particular limit to the upper limit of the elongation of the olefin resin contained in the resin coating satisfying (2) above, and it is usually 900% or less.
[0050] The elongation of the olefin resin that satisfies (2) above, as referred to in this specification, is the elongation until fracture when a tensile test is performed using a tensile testing machine with a tensile speed of 500 mm / min on a test piece made by punching a 1.0 mm thick sheet of olefin resin in a No. 3 dumbbell shape (or a cured sheet if the olefin resin is a curable resin).
[0051] As the olefin resin contained in the resin coating that satisfies (2) above, examples include the same substance as the cured product of the photocurable olefin resin previously exemplified as the substance contained in the resin coating that satisfies (1) above.
[0052] The resin coating layer satisfying (1) above and the resin coating layer satisfying (2) above can be formed, for example, by the following steps: in a state where a positive electrode, a negative electrode, a diaphragm, and an electrolyte are contained, a resin gasket is sandwiched between an outer can and a sealing can to seal it, and then a photocurable olefin resin (such as the above-mentioned photocurable resin composition) is coated on the exposed surface of the gasket to form a coating layer, and the photocurable olefin resin is cured by irradiating ultraviolet light or visible light to generate a cured product.
[0053] For example, when forming a resin coating using the above-described photocurable resin composition, the irradiation dose of ultraviolet or visible light is preferably 3 to 25 kJ / m². 2 .
[0054] From the viewpoint of better suppressing the intrusion of external moisture into the battery container, the thickness of the resin coating layer satisfying (1) and (2) above, as measured by the method shown in the examples described later, is preferably 50 μm or more, and more preferably 75 μm or more. There is no particular limitation on the upper limit of the thickness of the resin coating layer satisfying (1) and (2) above, but even if the thickness is increased too much, the effect will saturate, so it is usually 300 μm or less.
[0055] For the resin coating layer that satisfies (1) above and the resin coating layer that satisfies (2) above, the water vapor transmission rate is preferably 50 g / m³. 2 • Less than 24 hours (test environment: 85℃, relative humidity 85%, resin layer thickness: 1.0mm). It should be noted that the resin coating layer that meets the above (1) and the resin coating layer that meets the above (2) are preferably as impermeable to water vapor as possible, that is, their water vapor transmission rate is preferably as small as possible, or it can be 0g / m 2 ·24h.
[0056] The water vapor transmission rate of the resin coating referred to in this specification is the value measured according to the Japanese Industrial Standard (JIS) Z 0208 method (cup method) for a film peeled off from the substrate after the olefin resin is cured by coating a photocurable resin composition used to form the resin coating onto a substrate such as a resin film.
[0057] The button-type battery of the present invention may be, for example, an alkaline battery (alkaline primary battery, alkaline secondary battery) that uses an aqueous solution such as an alkaline electrolyte as the electrolyte (alkaline electrolyte).
[0058] The positive electrode of a button cell can be a positive electrode compound molded body that is formed into granules by molding a positive electrode compound containing a positive electrode active material, a conductive additive and a binder, or a positive electrode compound molded body with a positive electrode compound layer formed by the above positive electrode compound on one or both sides of the current collector.
[0059] Examples of positive electrode active materials include silver oxide (silver suboxide, silver oxide, etc.); silver-containing composite oxides [composite oxides of silver with cobalt, nickel or bismuth, etc. (silver-nickel composite oxide, silver-nickel-cobalt composite oxide, etc.)]; manganese dioxide; nickel hydroxyl oxide, etc.
[0060] When using silver oxide as the positive electrode active material, the silver oxide is preferably in particulate form. Typically, silver oxide is supplied as a fine powder with a particle size of 0.1 to 5 μm, but if the silver oxide is granulated and used in particulate form, the resistance is reduced compared to when it is used in the fine powder state, thus further improving the battery's load characteristics.
[0061] When using silver oxide in its powdered form, a larger amount of conductive additive is needed to reduce resistance. However, the carbon material preferred as the conductive additive has a low bulk density, so adding too much of it makes it difficult to increase the amount of silver oxide used as the active material. In contrast, using granular silver oxide improves weighability and reduces deviation. Furthermore, it improves filling and molding properties during pressure molding, thus reducing resistance. Additionally, when manufacturing multiple positive electrodes (and thus coin cells), the various characteristics become more stable. Furthermore, the amount of carbon material used as the conductive additive can be reduced, and the amount of silver oxide can be increased.
[0062] Furthermore, for example, silver oxide is reduced by reacting with carbon materials as shown in the following formula, thus reducing its discharge performance.
[0063] 2Ag₂O + C → 4Ag + CO₂
[0064] However, by forming silver oxide into particles, the above-mentioned reaction can be suppressed, and as mentioned above, the amount of carbon material added can also be reduced, thus further suppressing the reduction reaction of silver oxide, and the discharge characteristics (especially the low-temperature heavy load characteristics) become better.
[0065] When using granular silver oxide as the positive electrode active material, its particle size is preferably 50 μm or more, more preferably 75 μm or more, more preferably 500 μm or less, and more preferably 300 μm or less. Furthermore, its bulk density is preferably 1.5 g / cm³. 3 The above, more preferably 1.8 g / cm³ 3 The above is preferably 3.5 g / cm³. 3 The preferred value is 2.6 g / cm³. 3 The following applies. Silver oxide in this form exhibits better flowability compared to powdered silver oxide. As mentioned above, this improves weighability and formability, reduces resistance, and enhances reactivity, resulting in superior loading characteristics. Furthermore, the various characteristics of the manufactured cathode (and consequently, flat battery) are more stable. It should be noted that the particle size of the granular silver oxide referred to here is the number-average particle size calculated by measuring the number of particles (n) and the diameter (d) of each particle using a Honeywell Microtrac particle size analyzer "9320-X100" through laser scattering. Additionally, the bulk density of the granular silver oxide referred to here is the value obtained by placing a specified amount of granular silver oxide in a container and using a bulk density measuring device according to the bulk density determination method specified in JIS R 1628.
[0066] Conductive additives for positive electrode mixtures can include carbon blacks such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal cracking black; carbon materials such as carbon fiber; conductive fibers such as metal fibers; fluorinated carbon; metal powders such as copper and nickel; and organic conductive materials such as polyphenylene derivatives.
[0067] Examples of binders used as positive electrode binders include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), and polyvinylpyrrolidone (PVP).
[0068] In the case of a positive electrode compound molded body, it can be manufactured, for example, by pressing a positive electrode compound prepared by mixing a positive electrode active material, a conductive additive and a binder and an electrolyte (electrolyte) as needed into a specified shape.
[0069] In addition, in the case of a positive electrode having a positive electrode additive layer and a current collector, it can be manufactured by, for example, the following process: dispersing the positive electrode active material, conductive additive and binder in water or an organic solvent such as N-methyl-2-pyrrolidone (NMP) to prepare a composition (slurry, paste, etc.) containing a positive electrode additive (the binder can be dissolved in the solvent), coating it on the current collector and drying it, and performing pressing treatment such as calendering as needed.
[0070] However, the positive electrode is not limited to being manufactured by the methods mentioned above; it can also be manufactured by other methods.
[0071] As a component of the positive electrode mixture, the amount of positive electrode active material is preferably 80-98% by mass, the content of conductive additive is preferably 1.5-10% by mass, and the content of binder is preferably 0.5-10% by mass.
[0072] In the case of a positive electrode mixture molded body, its thickness is preferably 0.15 to 4 mm. On the other hand, in the case of a positive electrode having a positive electrode mixture layer and a current collector, the thickness of the positive electrode mixture layer (the thickness of each side of the current collector) is preferably 30 to 300 μm.
[0073] When a current collector is used at the positive electrode, examples of such current collectors include those made of stainless steel such as SUS316, SUS430, and SUS444; aluminum; and aluminum alloys. Examples of the current collector's form include plain-weave wire mesh, expanded metal, steel mesh, perforated metal, metal foam, and foil (plate). The thickness of the current collector is preferably, for example, 0.05 to 0.2 mm. It is also preferable to pre-coat the surface of such a current collector with a paste-like conductive material such as carbon paste or silver paste.
[0074] The negative electrode may use zinc particles, which are particles composed of pure zinc (containing unavoidable impurities) or zinc alloys. In such a negative electrode, the zinc in these particles functions as the active material. Examples of alloying components for zinc alloy particles include indium, bismuth, and aluminum (with the balance being zinc and unavoidable impurities). The zinc particles in the negative electrode may consist of only one type of particle or may contain two or more particles with different compositions.
[0075] However, zinc particles are preferably made from zinc that does not contain mercury as an alloying component. Batteries using such zinc particles can reduce environmental pollution caused by battery disposal. Furthermore, for the same reasons as with mercury, zinc particles are preferably made from zinc that does not contain lead as an alloying component.
[0076] Regarding the particle size of zinc particles, for example, it is preferable that the proportion of particles with a particle size of 75 μm or less in the total powder is 50% by mass or less, more preferably 30% by mass or less. Furthermore, the proportion of powder with a particle size of 100 to 200 μm can be 50% by mass or more, more preferably 90% by mass or more. The particle size of zinc particles referred to here is the value of 50% of the diameter in the cumulative fraction of the volume reference when calculating the integral volume from the smallest particle size using the same measuring apparatus as the above-described method for determining the average particle size of granular silver oxide. 50 ).
[0077] In addition to the zinc particles mentioned above, the negative electrode may contain a gelling agent (sodium polyacrylate, carboxymethyl cellulose, etc.) added as needed, or a negative electrode agent (gel-like negative electrode) formed by adding an alkaline electrolyte may be used. The amount of gelling agent in the negative electrode is preferably set to, for example, 0.5 to 1.5% by mass.
[0078] Alternatively, the negative electrode can be a non-gel-like negative electrode that substantially does not contain a gelling agent as described above. (Furthermore, in the case of a non-gel-like negative electrode, if the alkaline electrolyte present near the zinc particles does not thicken, a gelling agent may be present; therefore, "substantially does not contain a gelling agent" means that it can be present to a degree that does not affect the viscosity of the alkaline electrolyte). In the case of a gel-like negative electrode, the alkaline electrolyte exists near the zinc particles along with the gelling agent. Through the action of the gelling agent, the alkaline electrolyte thickens, and the movement of the alkaline electrolyte, and consequently the movement of ions in the electrolyte, is suppressed. Therefore, it can be considered that the reaction rate in the negative electrode is suppressed, which hinders the improvement of the battery's load characteristics (especially heavy load characteristics). In contrast, by making the negative electrode non-gel-like, the viscosity of the alkaline electrolyte present near the zinc particles is not increased, and the movement rate of ions in the alkaline electrolyte is kept relatively high, which can improve the reaction rate in the negative electrode and further improve the load characteristics (especially heavy load characteristics).
[0079] The alkaline electrolyte contained in the negative electrode can be the same substance as the alkaline electrolyte injected into the battery.
[0080] The zinc particle content in the negative electrode is preferably 60% by mass or more, more preferably 65% by mass or more, and preferably 75% by mass or less, more preferably 70% by mass or less.
[0081] The negative electrode preferably contains an indium compound. By containing an indium compound in the negative electrode, it is possible to more effectively prevent the generation of gas caused by the corrosion reaction between zinc particles and alkaline electrolyte.
[0082] Examples of indium compounds mentioned above include indium oxide and indium hydroxide.
[0083] The amount of indium compound used in the negative electrode, by mass ratio, is preferably 0.003 to 1 part relative to 100 parts of zinc particles.
[0084] As the alkaline electrolyte used in button batteries, aqueous solutions (alkaline electrolytes) of one or more alkali metal hydroxides (sodium hydroxide, potassium hydroxide, lithium hydroxide, etc.) are preferably used. From the viewpoint of obtaining an electrolyte with high conductivity, potassium hydroxide is particularly preferred; furthermore, from the viewpoint of further improving the leakage resistance of button batteries, sodium hydroxide is particularly preferred. Regarding the concentration of the alkaline electrolyte, for example, the concentration of potassium hydroxide in the aqueous solution of potassium hydroxide is preferably 20% by mass or more, more preferably 30% by mass or more, more preferably 40% by mass or less, and more preferably 38% by mass or less. Similarly, the concentration of sodium hydroxide in the aqueous solution of sodium hydroxide is preferably 15% by mass or more, more preferably 20% by mass or more, more preferably 35% by mass or less, and more preferably 30% by mass or less. By adjusting the concentrations of the aqueous solutions of potassium hydroxide and sodium hydroxide to such values, an alkaline electrolyte with excellent conductivity can be produced.
[0085] Alternatively, a gel electrolyte with a known gelling agent (sodium polyacrylate, carboxymethyl cellulose, etc.) added to an alkaline electrolyte as described above can be used as an alkaline electrolyte in a battery.
[0086] In the alkaline electrolyte, in addition to the components mentioned above, various known additives may be added as needed without impairing the effects of the present invention. For example, zinc oxide may be added to prevent corrosion (oxidation) of the zinc particles used in the negative electrode of the button cell. Alternatively, zinc oxide may also be added to the negative electrode.
[0087] In addition, when the button cell is a secondary battery, one or more of manganese compounds, tin compounds, and indium compounds can be dissolved in an alkaline electrolyte used as an alkaline electrolyte.
[0088] During discharge in an alkaline secondary battery with a positive electrode containing silver oxide as the positive electrode active material, silver is formed from the silver oxide at the positive electrode. However, when the battery is charged, silver oxide crystals form around the silver, thereby substantially reducing the reaction area of the positive electrode active material and hindering subsequent battery reactions. However, when these compounds are dissolved in an alkaline electrolyte, ions from these compounds (manganese ions, tin ions, indium ions) are adsorbed onto the positive electrode, thereby inhibiting the crystal growth of silver oxide and making the formed silver oxide crystals finer. Therefore, by suppressing the problem of silver oxide crystals forming during battery charging hindering battery reactions, the charge-discharge cycle characteristics of the secondary battery can be further improved, for example.
[0089] Examples of manganese compounds that dissolve in alkaline electrolytes include manganese chloride, manganese acetate, manganese sulfide, manganese sulfate, and manganese hydroxide. Similarly, examples of tin compounds that dissolve in alkaline electrolytes include tin chloride, tin acetate, tin sulfide, tin bromide, tin oxide, tin hydroxide, and tin sulfate. Furthermore, examples of indium compounds that dissolve in alkaline electrolytes include indium hydroxide, indium oxide, indium sulfate, indium sulfide, indium nitrate, indium bromide, and indium chloride.
[0090] From the viewpoint of better ensuring the above-mentioned effects, the concentration of indium compound, manganese compound and tin compound in alkaline electrolyte (its concentration when only one of them is dissolved, and their total concentration when two or more are dissolved) is preferably 50 ppm or more by mass, more preferably 500 ppm or more, and preferably 10,000 ppm or less, more preferably 5,000 ppm or less.
[0091] In button cell batteries, a separator is sandwiched between the positive and negative electrodes. Suitable separators for button cell batteries include nonwoven fabrics primarily composed of vinylon and rayon, vinylon-rayon nonwoven fabrics (vinylon-rayon blended paper), polyamide nonwoven fabrics, polyolefin-rayon nonwoven fabrics, vinylon paper, vinylon-cotton linter pulp paper, and vinylon-mercerized pulp paper. Alternatively, a membrane may be used as the separator, layered with a liquid-absorbing layer (electrolyte retention layer) such as a hydrophilically treated microporous polyolefin membrane (microporous polyethylene membrane, microporous polypropylene membrane, etc.), cellophane membrane, and vinylon-rayon blended paper. The separator thickness is preferably 20–500 μm.
[0092] In addition, when the button cell is a secondary battery, it is preferable to provide an anion-conducting membrane between the positive and negative electrodes. This anion-conducting membrane is based on a polymer and contains metal compound particles selected from at least one of metal oxides, hydroxides, carbonates, sulfates, phosphates, borates, and silicates.
[0093] Furthermore, in button cell batteries, it is preferable to pre-contain polyalkylene glycols or calcium compounds in at least one of the negative electrode, alkaline electrolyte, and separator. In this case, the growth of zinc dendrites in the negative electrode can be suppressed by the action of polyalkylene glycols and calcium compounds, thereby further improving the charge-discharge cycle characteristics (in the case of secondary batteries) and storage characteristics of the button cell battery.
[0094] The aforementioned polyalkylene glycols are compounds having a structure formed by the polymerization or copolymerization of alkylene glycols such as ethylene glycol, propylene glycol, and butylene glycol. They may have cross-linked structures, branched structures, or terminally substituted structures. As for the weight-average molecular weight, compounds with a weight-average molecular weight of approximately 200 or higher are preferred. There is no specific upper limit for the weight-average molecular weight. To more easily exert the effects brought about by its addition, the compound is preferably water-soluble, and a weight-average molecular weight of 20,000 or less is generally preferred, with a weight-average molecular weight of 5,000 or less being more preferable.
[0095] More specifically, in addition to preferably using polyethylene glycols (polyethylene glycol, polyethylene oxide, etc.) with a structure formed by the polymerization of ethylene glycol and polypropylene glycols (polypropylene glycol, polypropylene oxide, etc.) with a structure formed by the polymerization of propylene glycol, copolymers containing ethylene oxide units and propylene oxide units (polyoxyethylene polyoxypropylene glycol, etc.) can also be used.
[0096] When using polyalkylene glycols, the amount is preferably 0.01 to 1.5 parts by mass relative to 100 parts by mass of the aforementioned polyalkylene glycols.
[0097] In addition, examples of the aforementioned calcium compounds include calcium hydroxide, calcium oxide, calcium chloride, and calcium sulfate, which react with Zn(OH)4 generated during discharge. 2- The compound that reacts to form a complex compound such as CaZn(OH)4, and the complex compound itself, can preferably be made of calcium hydroxide and calcium oxide.
[0098] When using a calcium compound, the amount is preferably 5 to 40 parts by mass relative to 100 parts by mass of the calcium compound.
[0099] The outer casing for button batteries can be, for example, made of iron plated with nickel, or made of stainless steel.
[0100] Furthermore, the sealing plate for the button cell can be, for example, a sealing plate made of iron plated with nickel, or stainless steel. When the zinc particles, which are the negative electrode active material, are in direct contact with the inner surface of the sealing plate, it is preferable to form a metal layer made of copper or a copper alloy such as brass on the surface of the sealing plate on the side in contact with the negative electrode; more preferably, a tin layer is further formed on the surface of the aforementioned metal layer. Forming a metal layer made of copper or a copper alloy on the surface of the sealing plate on the side in contact with the negative electrode is to suppress the formation of localized cells with zinc and prevent zinc corrosion. Further forming a tin layer on the surface of the aforementioned metal layer can further improve the aforementioned corrosion resistance.
[0101] As gaskets for button batteries, examples include those made from nylon, polypropylene, and other similar materials.
[0102] Furthermore, the shape of a button battery when viewed from above can be circular, or it can be a polygon such as a quadrilateral (square, rectangle). In the case of a polygon, its corners can also be curved.
[0103] Example
[0104] The present invention will now be described in detail based on embodiments. However, the following embodiments do not limit the present invention.
[0105] Example 1
[0106] Silver oxide (Ag₂O) particles with an average particle size of 1.4 μm and containing 3.7% (by mass) Bi relative to the total silver content were mixed with carbon black particles (BET specific surface area of 68 m²). 2 A mixture was prepared by mixing acetylene black (g and an average particle size of 35 nm) at a mass ratio of 98:2.
[0107] Furthermore, the above mixture, graphite particles (BET specific surface area: 20m²) 2 A positive electrode mixture was prepared by mixing TiO2 particles (average particle size: 3.7 μm) and TiO2 particles (average particle size: 250 nm) in proportions of 95.2%, 3.8%, and 1% by mass, respectively. 300 mg of this positive electrode mixture was filled into a mold at a filling density of 5.7 g / cm³. 3 The positive electrode mixture is formed by pressing and shaping it into a circular plate with a diameter of 10.7 mm and a height of 0.6 mm.
[0108] The negative electrode active material uses mercury-free zinc alloy particles commonly used in alkaline primary batteries, containing 500 ppm In, 400 ppm Bi, and 10 ppm Al as additive elements. The average particle size (D) of the zinc alloy particles determined by the above method is... 50The proportion of particles with a diameter of 120 μm or less and a particle size of 75 μm or less is less than 25% by mass.
[0109] The zinc alloy particles and ZnO were mixed in a ratio of 97:3 (mass ratio) to obtain a composition for constituting the negative electrode (composition for negative electrode). 78 mg of this composition was weighed out for the preparation of the negative electrode.
[0110] The alkaline electrolyte is used in an aqueous solution containing potassium hydroxide at a concentration of 35% by mass and zinc oxide at a concentration of 3% by mass.
[0111] 5 g of aqueous dispersion of PTFE (solid content: 60% by mass), 2.5 g of aqueous solution of sodium polyacrylate (concentration: 2% by mass), and 2.5 g of hydrotalcite particles (average particle size: 0.4 μm) were mixed and rolled to produce a film with a thickness of 100 μm. The film was then cut into circles with a diameter of 11.3 mm to produce an anion-conductive membrane.
[0112] Two grafted films (thickness: 30 μm) composed of a graft copolymer having a structure that grafts acrylic acid onto the main chain of polyethylene are placed on both sides of a cellophane film (thickness: 20 μm). The resulting multilayer film is then stacked with vinylon-rayon blended paper (thickness: 100 μm), punched into a circle with a diameter of 11.3 mm, and then overlapped with the aforementioned anion-conductive membrane to form a diaphragm.
[0113] The positive electrode (positive electrode compound molding body), negative electrode (negative electrode composition), alkaline electrolyte, and separator are sealed within a battery container consisting of an outer can made of a steel plate with gold plating on the inner surface, a sealing plate made of a copper-stainless steel (SUS 304)-nickel clad plate, and an annular gasket made of nylon 66. It should be noted that the separator is configured such that the anion-conducting membrane is on the negative electrode side.
[0114] Next, a resin coating is formed on the exposed surface of the gasket in the battery container. The resin coating is formed as follows: UV-curable olefin resin "3175" manufactured by ThreeBond is applied to the exposed surface of the gasket at a concentration of 50 kJ / m². 2 The amount of ultraviolet light irradiated causes the olefin resin to solidify. This allows for the production of materials with... Figure 1 A button-type alkaline secondary battery with the same structure as shown, but with a diameter of 11.5 mm and a thickness of 3.0 mm. Additionally, for the cured olefin resin formed on the substrate under the same conditions as above, the Tg and elongation were measured, and the results were: Tg: 23.9 °C, elongation: 450%.
[0115] One of the manufactured button-type alkaline secondary batteries is cut off to obtain a result similar to... Figure 1The same cross-section as shown was observed using a microscope at 100x magnification. The thickness of the resin coating on the gasket was measured at five arbitrary locations using the microscope's scale, and the average of these measurements was taken as the thickness of the resin coating. The obtained thickness of the resin coating was 75 μm.
[0116] Example 2
[0117] As an alkaline electrolyte, a button-type alkaline secondary battery was prepared by further dissolving zinc oxide in an aqueous solution containing sodium hydroxide at a concentration of 26% by mass and then in an aqueous solution containing zinc oxide at a concentration of 3% by mass. Otherwise, the battery was prepared in the same manner as in Example 1.
[0118] Comparative Example 1
[0119] Except that no resin coating is formed on the exposed surface of the gasket, the button-type alkaline secondary battery is manufactured in the same manner as in Example 1.
[0120] Comparative Example 2
[0121] Except for forming an epoxy resin-based coating on the exposed surface of the gasket, which has a Tg of 61°C and an elongation of less than 200% as measured in the same manner as in Example 1, a button-type alkaline secondary battery is manufactured in the same manner as in Example 1.
[0122] Five button-type alkaline secondary batteries from Examples 1-2 and Comparative Examples 1-2 were prepared respectively. A charge-discharge cycle was performed, consisting of constant current discharge at 1.75 mA until the voltage reached 1.2V, followed by constant current-constant voltage charging at 3.5 mA until the voltage reached 1.8V, and then constant current-constant voltage charging at 1.8V until the current reached 0.35 mA. This cycle was repeated 10 times. The batteries were then stored at 60°C and 90% relative humidity, and the number of days until leakage was visually confirmed was measured. The average number of days measured for each battery was calculated, and the results are shown in Table 1.
[0123] [Table 1]
[0124]
[0125] As shown in Table 1, the batteries of Examples 1 and 2, which have a resin coating layer containing a cured olefin resin (an olefin resin having a Tg below 30°C and an elongation of over 300%) formed on the exposed surface of the gasket, effectively suppress the intrusion of external moisture into the battery container through the aforementioned resin coating layer. Therefore, compared with the batteries of Comparative Example 1 (which does not have a resin coating layer) and Comparative Example 2 (which uses epoxy resin to form a resin coating layer), the number of days until leakage occurs is longer, demonstrating excellent leakage resistance.
[0126] Furthermore, the battery of Example 2, which uses an alkaline electrolyte containing sodium hydroxide, exhibits improved leakage resistance compared to the battery of Example 1, which uses an alkaline electrolyte composed of an aqueous potassium hydroxide solution and does not contain sodium hydroxide.
[0127] Example 3
[0128] As an alkaline electrolyte, an aqueous solution of potassium hydroxide with a concentration of 36% by mass was prepared, containing 4% by mass zinc oxide and 1000 ppm indium hydroxide.
[0129] Next, a mixture containing 78% by mass of granulated silver oxide (average particle size 150 μm), 20.7% by mass of manganese dioxide, 1.2% by mass of graphite, and 0.1% by mass of low molecular weight polytetrafluoroethylene ("LUBRON" L-5, manufactured by Daikin Industries, Ltd.) is filled into a mold and pressurized to produce a positive electrode consisting of a circular plate-shaped compound with a diameter of 7.5 mm and a height of 0.48 mm. The resulting positive electrode is then placed inside the inner bottom of an outer packaging can (described later) and partially impregnated with the aforementioned electrolyte for battery assembly.
[0130] The negative electrode uses mercury-free zinc alloy particles commonly used in alkaline primary batteries, containing 500 ppm In, 100 ppm Bi, and 10 ppm Al as additive elements. The average particle size (D) of the zinc alloy particles determined by the above method is... 50 The particle size is 120 μm, and the proportion of particles with a diameter of less than 75 μm is 25% by mass.
[0131] For the separator, a laminate (manufactured by GS Yuasa Membrane Co., Ltd., "YG 2122") consisting of a grafted membrane (thickness: 30 μm) and a cellophane membrane (thickness: 20 μm) was cut into circles with a diameter of 7.7 mm and used. The grafted membrane was composed of a graft copolymer having a structure in which acrylic acid was graft copolymerized onto the polyethylene backbone. In addition, a 200 μm thick vinylon-rayon blended paper cut into circles with a diameter of 7.7 mm was used as the electrolyte retention layer.
[0132] The battery is assembled as follows using an outer can made of SUS430 and a sealing can made of copper-stainless steel (SUS304)-nickel composite plate.
[0133] After inserting a nylon 66 annular gasket into the sealed container, 29.5 mg of zinc alloy particles, which form the negative electrode, are placed on the inner bottom surface of the sealed container. Then, 15 μL of alkaline electrolyte is added. On the negative electrode, a vinylon-rayon blended paper, a grafted film / glass paper laminate, and an outer container for holding the positive electrode are sequentially stacked and sealed. Then, a resin coating layer is formed on the exposed surface of the gasket, similar to Example 1, thereby assembling a button-type alkaline battery (primary battery) with a diameter of 7.9 mm and a thickness of 1.68 mm.
[0134] Comparative Example 3
[0135] Except that no resin coating is formed on the exposed surface of the gasket, the button-type alkaline battery is assembled in the same manner as in Example 3.
[0136] The button-type alkaline batteries of Example 3 and Comparative Example 3 were stored in a constant temperature bath at 60°C for a specified time, and the discharge capacity after storage was calculated to investigate the change in discharge capacity caused by high-temperature storage. It should be noted that since the batteries were stored without humidification in the constant temperature bath, the relative humidity in the constant temperature bath during storage was approximately 10%.
[0137] For each storage condition, tests were conducted using four batteries. The average of the measured discharge capacity was calculated, and the ratio of the discharge capacity to the initial discharge capacity was used as the capacity retention rate. The results are presented below. Figure 2 .
[0138] In the battery of Comparative Example 3, by storing the battery under conditions without humidification, the water in the electrolyte gradually escaped from the battery system, resulting in a state of liquid depletion. Therefore, it was confirmed that the longer the storage period, the greater the capacity reduction of the battery. On the other hand, in the battery of Example 3, by forming a resin coating layer containing a photocurable olefin resin (an olefin resin having a Tg of less than 30°C and an elongation of more than 300%) on the exposed surface of the gasket, it was possible to suppress the escape of water in the electrolyte from the gasket to the battery system, and thus suppress the capacity reduction of the battery.
[0139] As can be seen from the above results, the present invention can inhibit the intrusion of moisture from the outside to the inside of the battery and conversely inhibit the outflow of moisture from the inside to the outside, thereby improving the storage characteristics of the battery.
[0140] This invention can also be implemented in ways other than those described above without departing from its spirit. The embodiments disclosed in this application are examples, and the invention is not limited to these embodiments. The scope of the invention is interpreted preferentially to the appended claims compared to the description in the foregoing specification, and all modifications within the scope of the claims are included in the claims.
[0141] Industrial availability
[0142] The button cell battery of the present invention can be used for the same purposes as various known batteries (alkaline primary batteries, alkaline secondary batteries, etc.).
[0143] The button-type battery of this invention can contribute to achieving the 17 Sustainable Development Goals (SDGs) set by the United Nations: Goal 3 (ensuring healthy lives and promoting well-being for all people of all ages), Goal 7 (ensuring access to affordable, reliable and sustainable modern energy for all), Goal 11 (building inclusive, safe and resilient sustainable cities and human settlements), and Goal 12 (ensuring sustainable production and consumption patterns).
[0144] Explanation of reference numerals in the attached figures
[0145] 1: Button cell battery, 2: Outer can, 3: Sealed can, 4: Positive electrode, 5: Negative electrode, 6: Separator, 7: Gasket, 8: Resin coating.
Claims
1. A button cell battery comprising a battery container, wherein a positive electrode, a negative electrode, and an electrolyte are disposed inside the battery container, the battery container having an outer can and a sealed can, and a resin gasket between the outer can and the sealed can, characterized in that, A resin coating is formed on the exposed surface of the gasket. The resin coating is a cured product of a photocurable olefin resin.
2. The button cell battery according to claim 1, wherein, The cured material has a glass transition temperature below 30°C.
3. The button cell battery according to claim 1, wherein, The cured material has an elongation of over 300%.
4. A button cell battery comprising a battery container, wherein a positive electrode, a negative electrode, and an electrolyte are disposed inside the battery container, the battery container having an outer can and a sealed can, and a resin gasket between the outer can and the sealed can, characterized in that, A resin coating is formed on the exposed surface of the gasket. The resin coating contains an olefin resin having a glass transition temperature below 30°C and an elongation of over 300%.
5. The button cell battery according to claim 1 or 4, wherein, The electrolyte is an alkaline electrolyte.
6. The button cell battery according to claim 5, wherein, The alkaline electrolyte contains sodium hydroxide.
7. The button cell battery according to claim 1 or 4, wherein, The thickness of the resin coating is 50 μm or more.
8. A method for manufacturing a button cell battery, the button cell battery comprising a battery container, and having a positive electrode, a negative electrode, and an electrolyte disposed inside the battery container, the battery container having an outer can and a sealed can, and a resin gasket between the outer can and the sealed can, characterized in that, The manufacturing method has the following characteristics: The process of sealing by inserting a resin gasket between the outer can and the sealing can. The process of forming a light-curable olefin resin coating layer on the exposed surface of the sealed gasket, and The process of curing the olefin resin.
9. The method for manufacturing a button cell battery according to claim 8, wherein, An alkaline electrolyte containing sodium hydroxide is used as the electrolyte.
Citation Information
Patent Citations
Electrochemical cell and its manufacturing method
JP2007035829A